The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/codi.12757
|View full text |Cite
|
Sign up to set email alerts
|

Major postoperative complications following elective resection for colorectal cancer decrease long‐term survival but not the time to recurrence

Abstract: Non-lethal major postoperative complications seem to have a negative long-term impact on survival but not on time to recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 37 publications
5
34
1
3
Order By: Relevance
“…We observed a tendency for these indices to over-predict the expected mortality and morbidity as compared to that actually observed (29). Postoperative morbidity was higher in the right hemicolectomies, which is in agreement with the data from several studies (30). This has been linked to older age, the need for blood products during surgery and a greater number of open surgeries at this location (30,31).…”
Section: Discussionsupporting
confidence: 90%
“…We observed a tendency for these indices to over-predict the expected mortality and morbidity as compared to that actually observed (29). Postoperative morbidity was higher in the right hemicolectomies, which is in agreement with the data from several studies (30). This has been linked to older age, the need for blood products during surgery and a greater number of open surgeries at this location (30,31).…”
Section: Discussionsupporting
confidence: 90%
“…Selected papers, published between 2011 and 2016, are summarized in Table 3, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55. These studies were cohort studies that conducted risk adjustment using multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that employing fast track therapy in the treatment of older patients was not only feasible, but might also reduce the number of general complications and the duration of hospital stay. Moreover, there are several studies showing that postoperative complication could decrease survival [1920]. Carefully considering from these results, movements to accelerate recovery after surgery could be a factor that might affect survival.…”
Section: Discussionmentioning
confidence: 99%